The Views of NU Ulama in Medan about Polygamy - Edi Sahputra Siregar (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2020)
This study uses a perspective that uses a combination of theories polygamy normative scientific perspective, the opinion of the scholars and the phenomenon of reality as viewed by scholars NU in Medan. Generally found that the views of the scholars NU Medan on polygamy is something that is permissible on the basis of the text of the Quranic verse of Surat an-Nisa ', paragraph 3 which makes the fair as an essential prerequisite skill, because polygamy is a kemslahatan and also a solution to solve the problem, sehinggah polygamy is allowed to be done but it must first be discussed with the family without needing any government intervention to deal with it, because they consider the legislation only complicates something that has obviously legal skill in the Qur'an.